2015
DOI: 10.1614/wt-d-14-00021.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of WideStrike Cotton Response to Repeated Applications of Glufosinate at Various Application Timings

Abstract: Glyphosate-resistant (GR) weeds are most challenging for growers to control in cotton in the midsouth region of the United States. As a result, growers in these states are transitioning from a glyphosate-based system to a glufosinate-based system. A field study was conducted in 2010 and 2011 in Georgia, North Carolina, and Tennessee to determine the effect of repeated glufosinate applications to WideStrike cotton applied at various application timings. One to three glufosinate applications at 594 g ai ha−1were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
2
4
1
Order By: Relevance
“…Visual Injury Ratings. Visual injury ratings captured from the WideStrike (PHY 333 WRF) treatments are consistent with injury reported by Steckel et al (2012) and Culpepper et al (2009), slightly higher than those observed by Barnett et al (2015), and lower than those observed by Stewart et al (2013). Steckel et al (2012) reported 18 and 23% average injury from glufosinate and glufosinate plus S-metolachlor, respectively.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Visual Injury Ratings. Visual injury ratings captured from the WideStrike (PHY 333 WRF) treatments are consistent with injury reported by Steckel et al (2012) and Culpepper et al (2009), slightly higher than those observed by Barnett et al (2015), and lower than those observed by Stewart et al (2013). Steckel et al (2012) reported 18 and 23% average injury from glufosinate and glufosinate plus S-metolachlor, respectively.…”
Section: Discussionsupporting
confidence: 85%
“…reported 14% and 20% injury from a single application of glufosinate and an application of glufosinate plus S-metolachlor, respectively, but application rates of glufosinate in their studies were lower (430 g ai ha -1 instead of 594 g ai ha -1 ). Barnett et al (2015) applied glufosinate at similar application rates but noted less injury (11% max at 5 DAA). Differences in injury could be due to differences in tested cultivars and environmental conditions surrounding the application timing or the growth stage; in this study, sequential applications were stacked at the end of the application window.…”
Section: Discussionmentioning
confidence: 92%
“…These authors also reported cotton yield reduction for glufosinate þ glyphosate (1,200 kg ha -1 ), glufosinate þ S-metolachlor (1,250 kg ha -1 ), and glufosinate þ glyphosate þ S-metolachlor (1,170 kg ha -1 ) tank mixtures when compared to the control (1,470 kg ha -1 ). Barnett et al (2015) reported 3% to 11% injury to WideStrike® cotton following POST applications of glufosinate, where higher injuries were observed with multiple glufosinate applications. These authors also observed that one, two, and three POST glufosinate applications negatively influenced cotton height and NACB, whereas three glufosinate applications reduced cotton yield (Barnett et al 2015).…”
Section: Plant Growth and Development Parametersmentioning
confidence: 99%
“…Barnett et al (2015) reported 3% to 11% injury to WideStrike® cotton following POST applications of glufosinate, where higher injuries were observed with multiple glufosinate applications. These authors also observed that one, two, and three POST glufosinate applications negatively influenced cotton height and NACB, whereas three glufosinate applications reduced cotton yield (Barnett et al 2015). Applications of glufosinate þ glyphosate increased crop injury observed herein at 3 (27%) and 7 DAA (16%) when compared to applications of the two respective herbicides alone (18% and 11% for glufosinate; and 13% and 8% for glyphosate) (Table 3).…”
Section: Plant Growth and Development Parametersmentioning
confidence: 99%
“…One to two postemergence applications of glufosinate to WideStrike cotton have been documented to cause visible plant injury ranging from 5% to 25% without having a negative effect on yield (Culpepper et al 2009;Dodds et al 2015;Whitaker et al 2011a). Three applications of glufosinate to WideStrike cotton, however, have been shown to reduce yield up to 7% (Barnett et al 2015). Glufosinate applications in combination with other herbicides have also been shown to delay cotton maturity and reduce yield (Steckel et al 2012).…”
Section: Introductionmentioning
confidence: 99%